Examining the Implementation of Different Test Tasks in Assessing EFL Learners’ Use of English Tenses - GRIDI , Mehdi (Journal of Human Sciences, 2023)
This study examines how different tasks assess learners’ use of English tenses. EFL teachers use test tasks such as gap-filling, multiple-choice and grammaticality judgment tasks. To check how these three types of tasks assess the uses of tenses, three tests about present, past and future tenses –each including the three tasks- are given to 29 second year EFL learners at the Teachers’ Training School Assia Djebar, Constantine, Algeria. The results reveal the highest scores are in the multiple-choice task and the lowest in the grammaticality judgement task, and that the high scores obtained in the multiple-choice task do not reflect mastery of the uses of English tenses because there is no agreement between all the scores obtained. The results show that assessment of the uses of tenses should include different task types to have a comprehensive view of learners’ knowledge of English tenses.